1977
DOI: 10.1111/j.1365-2125.1977.tb04518.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results with beclomethasone dipropionate aerosol in children with bronchial asthma: why does it sometimes fail?

Abstract: 1. Beclomethasone dipropionate aerosol has been shown to be a highly effective treatment for asthma in childhood, with virtual absence of side effects at this age. 2. When treatment is unsuccessful, this is usually due to failure to take it correctly and regularly. 3. A good response is usually associated with an improvement in ventilatory function and a marked increase in growth velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…In an earlier report (5) the number of hospital admissions was similar to that during the period before BDA treatment and in another study (10) it is suggested that failure to respond to BDA treatment might be due to psychosocial factors, fn the present study there was a decrease by 53% in the number of acute visit to the outpatient clinics and by 63% in the number of acute admissions to hospital. In an earlier report (5) the number of hospital admissions was similar to that during the period before BDA treatment and in another study (10) it is suggested that failure to respond to BDA treatment might be due to psychosocial factors, fn the present study there was a decrease by 53% in the number of acute visit to the outpatient clinics and by 63% in the number of acute admissions to hospital.…”
Section: Discussionsupporting
confidence: 83%
“…In an earlier report (5) the number of hospital admissions was similar to that during the period before BDA treatment and in another study (10) it is suggested that failure to respond to BDA treatment might be due to psychosocial factors, fn the present study there was a decrease by 53% in the number of acute visit to the outpatient clinics and by 63% in the number of acute admissions to hospital. In an earlier report (5) the number of hospital admissions was similar to that during the period before BDA treatment and in another study (10) it is suggested that failure to respond to BDA treatment might be due to psychosocial factors, fn the present study there was a decrease by 53% in the number of acute visit to the outpatient clinics and by 63% in the number of acute admissions to hospital.…”
Section: Discussionsupporting
confidence: 83%
“…Clinical response was good in all three groups but the inci dence of unwanted systemic side effects in the prednisone-treated group was nearly six times that during inhalation therapy. Nonetheless, not all asthmatics respond adequately to inhalations alone [7,9,10,14,16,20] but still require oral steroids, al beit generally at lower dosage. There is therefore still a need for oral steroids in the treatment of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, beclomethasone di propionate [7,13,14,16,[19][20][21]25] and betamethasone valerate [2,6,[9][10][11]15] have been extensively used as inhalations in asthma. The main objectives have been to try to reduce the amount of oral steroids being taken by steroid-dependent asth matics and hence hopefully improve their HPA-axis suppression, or to use inhala tions in children in the hope of controlling the symptomatology without suppressing the adrenal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…2 It has recently been reported by several investigators that many patients are noncompliant in the use of their aerosols. [2][3][4][5][6][7] Paterson and Crompton brought this to the attention of the medical community when they interviewed and observed 321 asthmatic patients in the use of their inhalers. All patients reportedly had been counseled in the correct technique of aerosol administration by members of the medical staff before treatment was initiated.…”
Section: The Introduction Of Beclomethasone Dipropionatementioning
confidence: 99%